2019
DOI: 10.1002/ece3.5180
|View full text |Cite
|
Sign up to set email alerts
|

Infection sequence alters disease severity—Effects of the sequential exposure of two larval trematodes to Polypedates cruciger tadpoles

Abstract: Multiple pathogens coexist in nature, and hence, host species often encounter several pathogens simultaneously. The sequence in which the host encounters the parasites influences interactions between parasites and host pathology. Here, the effects of infection by two cercaria (larvae of trematodes) types, pleurolophocercous cercaria of Acanthostomum burminis and a furcocercous cercaria, on the tadpoles of common hourglass tree frog (Polypedates cruciger) were examined. Ten days posthatch, tadpoles (Gosner stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Although there are many records of abnormal amphibians in Eurasia [1], only some cases of trematode-dependent anomalies were strongly supported by laboratory experiments [20][21][22][23][24][25]. Here, we describe new variants of morphological anomalies caused by the trematode Strigea robusta in Eurasian amphibians.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although there are many records of abnormal amphibians in Eurasia [1], only some cases of trematode-dependent anomalies were strongly supported by laboratory experiments [20][21][22][23][24][25]. Here, we describe new variants of morphological anomalies caused by the trematode Strigea robusta in Eurasian amphibians.…”
Section: Introductionmentioning
confidence: 78%
“…Recent studies have shown that, in several amphibian species, the anomalies can be caused by some species of trematodes [13][14][15][16][17][18][19][20][21][22][23][24][25]. The most investigated cases concerned the trematode Ribeiroia ondatrae in many amphibian populations across the USA and Canada [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the magnitude of this facilitation depended on infection sequence. There is growing evidence that infection sequence can determine the magnitude and direction of the effect of within-host microbial interactions [42,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The direction and magnitude of interactions among parasites and hostassociated microbiota may depend on the sequence in which they infect host individuals [41][42][43][44][45]. While simultaneous coinfections can occur in nature [46], more often, microbes infect a host at different time points [41].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of infection order has been discussed in the case of the parasite coinfections (35) . Recently, it was shown that the sequence of larval trematodes in tadpoles could also affect the disease severity (36) . In a different in vitro study in swine alveolar macrophages, the infection order of porcine circovirus type 2 and porcine reproductive and respiratory syndrome virus affected the cytokine response (37) .…”
Section: Discussionmentioning
confidence: 99%